Irradiated Gao Miao Zi Bentonite for Uranium Retention: Performance and Mechanism - Yushan Zhang; Gang Song; Yujie Mo; Shuwen Wang; Diyun Chen; Minhua Su (Separations)
Bentonite has been considered as backfill material in the long-term deep geological disposal sites for radioactive waste. The performance of raw and irradiated bentonite based on the retention of radioactive nuclides, such as U(VI), is a critical factor for its application. Herein, the intrinsic features and adsorption behavior of Gao Miao Zi (GMZ) bentonite based on uranyl ions was investigated. In aqueous solutions, bentonite can achieve an adsorption rate of up to 100% for U(VI). The primary mechanism of U(VI) adsorption by GMZ bentonite is ion exchange, supplemented by surface complexation. Strong irradiation can introduce slight structural changes and framework fractures in bentonite, reducing its adsorption capacity for U(VI). This study provides an in-depth analysis of the adverse effects of high doses of radiation (100 kGy) on the microstructure and adsorption properties of bentonite, offering important insights for the safe storage of radioactive waste.